Meeting report: 6th Global Forum on Tuberculosis Vaccines, 22–25 February 2022, Toulouse, France. (April 2023) - Young, Carly; Suliman, Sara; Rozot, Virginie; Mendelsohn, Simon C.
Highlights: The 6th Global Forum on TB Vaccines convened virtually from 22 to 25 February 2022. The TB R&D landscape was explored under the theme "New horizons for TB vaccines". This report highlights key themes, progress, and gaps in the TB vaccine field. Sessions included cutting-edge preclinical and clinical vaccine research. New TB vaccine preparedness and advocacy were highlighted as urgent issues. Abstract: Safe, effective, and accessible vaccines are urgently needed to end tuberculosis (TB) by 2030. The 6 th Global Forum on TB Vaccines, convened virtually 22–25 February 2022, was hosted by Toulouse, France, under the high patronage of President Emmanuel Macron, and the patronages of Minister for Solidarity and Health, Olivier Véran, and Minister for Higher Education, Research and Innovation, Frédérique Vidal. The theme for the meeting, "New horizons for TB vaccines", reflected the changing landscape in which TB vaccine research and development (R&D) is being conducted: TB vaccines advancing into late-stage clinical trials and toward licensure, innovative research toward diversifying the TB vaccine pipeline and developing the next generation of candidates, increasing political, civil society, and community support for TB vaccines, and the ongoing COVID-19 pandemic. In this report, we summarize key themes and findings from the meeting, highlighting progress and gaps in the TB vaccine field.